2023
DOI: 10.3390/ijms24065465
|View full text |Cite
|
Sign up to set email alerts
|

Tactics with Prebiotics for the Treatment of Metabolic Dysfunction-Associated Fatty Liver Disease via the Improvement of Mitophagy

Abstract: Mitophagy/autophagy plays a protective role in various forms of liver damage, by renovating cellular metabolism linking to sustain liver homeostasis. A characterized pathway for mitophagy is the phosphatase and tensin homolog (PTEN)-induced putative kinase 1 (PINK1)/Parkin-dependent signaling pathway. In particular, PINK1-mediated mitophagy could play an indispensable role in improving the metabolic dysfunction-associated fatty liver disease (MAFLD) which could precede to steatohepatitis (NASH), fibrosis, and … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
9
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 13 publications
(10 citation statements)
references
References 128 publications
1
9
0
Order By: Relevance
“…[59][60][61] By modifying or inhibiting the PI3K/AKT/mTOR pathway, various potential inhibitors, such as some natural compounds, offer the ability to prevent HSC activation and liver fibrosis. [62][63][64][65][66][67] In our study, the exogenous addition of Thbs1 to induce mouse primary HSCs activation demonstrated that Thbs1 could activate HSC by promoting this signaling pathway. In contrast, pharmacological inhibition of this pathway eliminated the effect of Thbs1 activation of HSCs.…”
Section: Discussionmentioning
confidence: 52%
See 1 more Smart Citation
“…[59][60][61] By modifying or inhibiting the PI3K/AKT/mTOR pathway, various potential inhibitors, such as some natural compounds, offer the ability to prevent HSC activation and liver fibrosis. [62][63][64][65][66][67] In our study, the exogenous addition of Thbs1 to induce mouse primary HSCs activation demonstrated that Thbs1 could activate HSC by promoting this signaling pathway. In contrast, pharmacological inhibition of this pathway eliminated the effect of Thbs1 activation of HSCs.…”
Section: Discussionmentioning
confidence: 52%
“…The PI3K/AKT signaling cascade has been shown to facilitate HSC activation and collagen synthesis in response to various proproliferative and fibrotic stimuli in earlier investigations 59–61 . By modifying or inhibiting the PI3K/AKT/mTOR pathway, various potential inhibitors, such as some natural compounds, offer the ability to prevent HSC activation and liver fibrosis 62–67 . In our study, the exogenous addition of Thbs1 to induce mouse primary HSCs activation demonstrated that Thbs1 could activate HSC by promoting this signaling pathway.…”
Section: Discussionmentioning
confidence: 54%
“…Restoration of mitochondrial function by small molecules attenuates oxidative stress, and mitophagy is thus normalized. For instance, natural products (flavones) lower reactive oxygen species [ 93 ], and prebiotics improve mitophagy to ameliorate NASH [ 94 ]. Nevertheless, their benefits are mediated by non-specific mechanisms.…”
Section: The Novel Nash Targets Regulate Mitochondrial Function and E...mentioning
confidence: 99%
“…In addition, several studies have investigated the advantages of combining these natural compounds with chemotherapeutic drugs. In particular, more and more phytochemicals are now applied to the treatment of metabolic diseases [97,98]. Therefore, it might be necessary to have a more comprehensive understanding of the potential mechanisms of various diseases.…”
Section: Future Perspectives Of Chitosanmentioning
confidence: 99%